A comparative study on the machinability of β-type novel Ti29Nb13Ta4.6Zr (TNTZ) biomedical alloys under micro-milling operation. (28th April 2023) - Aslantas, Kubilay; Demir, Bilge; Guldibi, Ahmet Serdar; Niinomi, Mitsuo; Dikici, Burak
Abstract: β-type Ti29Nb13Ta4.6Zr (TNTZ) alloy is a new-generation alloy that does not contain toxic/allergic elements. The alloys have low Young's modulus (⁓60 GPa) close to the cortical bone, providing excellent biocompatibility over familiar commercial CP Ti or Ti6Al4V ELI. Different macro/micro-machining methods can be used to obtain the final shape of Ti alloys and impact on the implant's bio ecosystem and performance. This study compared the micro-mill machining performance of the TNTZ alloys with commercial CP Ti and Ti6Al4V ELI. Machining experiments were performed under similar and different cutting speeds and constant feed rate conditions. In the study, cutting forces, surface roughness, burr size and tool wear were obtained. The results showed that the Fx cutting forces for TNTZ are about 3 and 2 times higher than for CP Ti and Ti6Al4V alloys, respectively. Depending on the increasing cutting distance, the surface roughness of CP Ti and Ti6Al4V materials followed a similar trend. However, the surface roughness values for TNTZ alloy are higher and decrease with increasing cutting distance. Burr widths for CP Ti and Ti6Al4V are similar, but the milling direction at which maximum burr occurs varies. In the TNTZ alloy, the burr width is about 3 times higher, and the burr occurred inside the slot, not at the edge of the machined slot. The predominant type of damage in milling Ti6Al4V and CP Ti materials is abrasive and adhesive. The dominant damage type in TNTZ alloy is chipping. Increasing the number of revolutions in TNTZ causes the cutting forces and burr width to increase.